"Acceptable" Versus "Understandable": The Impact of Adjective Choice in Survey Research on Public Attitudes Towards Sex Work - Johansson, Isabelle; Hansen, Michael A. (Springer Science and Business Media LLC, 2026)
Research on public attitudes towards sex work has sought to understand the relationship between question wording, aggregate levels of support, and predictors of attitudes. Recent studies have found that the terminology used to represent the activity can have substantial implications for findings. Given that cross-national research often employs varying descriptors due to translation or cultural nuance, our study addresses a gap in the literature by clarifying how adjective choice shapes measured attitudes. Using a quota-based sample in a pre-registered survey experiment, we assessed whether subtle differences in adjective choice (“acceptable” vs. “understandable”) in survey questions impact public attitudes. Our results indicate that using understandable elicits more positive responses than acceptable. Predictors of attitudes also vary based on the adjective used: religiosity was a stronger predictor for acceptable, while hostile sexism predicted attitudes only for understandable. Even after accounting for these differences, aggregate positive views were substantially higher when understandable was used. These findings suggest that sex work might not be a politically salient or personally crystallized issue for most people and that attitudes toward sex work are relatively fluid, highlighting the importance of precise wording in survey research.